Customer Product Choice: The Effect of Product Quality on Relative price and Price fairness and their implication on Customer Product Choice - Dudung Juhana (Jurnal Computech & Bisnis (e-journal), 2023)
This study examines the influence of product quality on individuals' perceptions of relative prices and price justice, as well as the potential consequences for consumer decision-making in product selection. This study employs robust statistical analysis to get insights into customers' decision-making processes when purchasing products and selecting brands, particularly about product attributes and pricing. The study employed a non-parametric Structural Equation Modeling PLS technique, which involved a sample of 100 consumers who had previously consumed cigarette goods in the urban area of Bandung. The questionnaire was distributed through social media platforms, utilizing a Google Form link. The employed sample method is convenience sampling, wherein clients are requested to complete a structured questionnaire that has been supplied. The poll encompassed inquiries about participants' perceptions regarding the quality of the product, its comparable pricing, and the appropriateness of the price. The survey data were subjected to rigorous statistical analysis, encompassing several analytical techniques such as regression analysis and hypothesis testing. The study's findings indicate that a product's quality plays a substantial role in shaping consumers' evaluations of comparable prices and perceptions of price justice. Consumers tend to make product selections predicated upon their subjective quality assessment, shaping their perception of the product's price. The presence of excellent product quality can mitigate price barriers, as customers exhibit a greater propensity to pay elevated costs for things they believe to possess superior quality. Furthermore, this study demonstrates that comparable costs and the perception of price justice influence consumer product choices. This condition highlights the significance of prudent pricing within a company's marketing strategy, whereby competitive and equitable pricing can catalyze consumers to opt for specific products. However, a further noteworthy discovery is that the relative pricing and price reasonableness factors do not influence customers' brand preferences. This condition suggests that when considering the choice of a brand, several elements, such as brand image, individual preferences, or distinctive brand characteristics, may exert a more significant impact. The correlation between product and brand compatibility plays a significant part in consumers' decision-making process when it comes to selecting a brand. The findings of this study offer significant implications for businesses in enhancing their marketing and pricing strategies. Furthermore, they contribute to a more comprehensive comprehension of consumer decision-making processes within the product and brand choices framework. In order to achieve success in a competitive and dynamic business climate, it is imperative to possess a comprehensive comprehension of the various elements that impact consumer decision-making.